Palpebral Kista Dermoid - Witjaksana, Riani; Amalia, Husnun; Hairunisa, Nany; Kartadinata, Erlani; Adhiwardan, Anggraeni; Prasetyaningsih, Noviani (Jurnal Biomedika dan Kesehatan, 2024)
Dermoid and epidermoid cysts are prevalent benign orbital tumors in childhood, representing 3-9% of pediatric ocular tumors. Occasionally, dermoid cysts can attain significant size, leading to cosmetic deformities. A precise surgical approach to dermoid cysts can lead to considerable cosmetic improvement for the patient. A 19-year-old female presented with swelling in the outer corner of her left eye, accompanied by minor discomfort in the affected area. Upon ophthalmologic examination 1.5x1 cm masses were detected in the upper left eyelid near the lateral canthus Clinical diagnosis of Dermoid cyst left eye upper eyelid made. Subsequently, a surgical excision under general anesthesia was scheduled. During the procedure, the cyst was successfully excised while preserving the cyst wall integrity. The conclusion is imperative for ophthalmologists to recognize the necessity of precisely performing surgical excision of these cysts to achieve favorable functional and aesthetic outcomes.